High‐Loading, Well‐Dispersed Phosphorus Confined on Nanoporous Carbon Surfaces with Enhanced Catalytic Activity and Cyclic Stability. Issue 12 (27th October 2021) - Meng, Juan; Liu, Yongzhuang; Xia, Qinqin; Liu, Shi; Tong, Zhihan; Chen, Wenshuai; Liu, Shouxin; Li, Jian; Dou, Shuo; Yu, Haipeng
Abstract: Phosphorus‐doped carbon materials are promising alternatives to noble metal‐based catalysts for the highly selective oxidation of benzyl alcohol to benzaldehyde, but it is challenging to achieve high loadings of high‐activity P dopants in metal‐free catalysts. Here, the preparation of high‐loading and well‐dispersed P atoms confined to the surfaces of cellulose‐derived carbon via a dissolving‐doping strategy is reported. In this method, cellulose is dissolved in phosphoric acid to generate a cellulose‐phosphoric supramolecular collosol, which is then directly carbonized. The as‐prepared carbon possesses a high specific surface area of 1491 cm 3 g −1 and a high P content of 8.8 wt%. The P‐doped nanoporous carbon shows a superior catalytic activity and cyclic stability toward benzyl alcohol oxidation, with a high turnover frequency of 3.5 × 10 −3 mol g −1 h −1 and a low activation energy of 35.6 kJ mol −1 . Experimental results and theoretical calculations demonstrate that the graphitic C3 PO species is the leading catalytic active center in this material. This study provides a novel strategy to prepare P dopants in nanoporous carbon materials with excellent catalytic performance. Abstract : Cellulose‐phosphoric supramolecular collosol precursor is prepared to derive nanoporous P‐doped carbon with a large specific surface area, high‐loading, and well‐dispersed dopants. The P‐doped carbon exhibits superior catalytic activity and cycling stability toward selective oxidation of alcohols to aldehydes. Theoretical calculation and experimental results prove that the C3 PO species is the critical catalytic active center.